Mechanical and thermal properties of a biocomposite based on polyvinylchloride/epoxidized natural rubber blend reinforced with rice husk microfiller. (September 2021) - Bui, QB; Colin, J; Nguyen, TD; Mao, ND; Nguyen, TML; Perré, P
In this study, a biocomposite material derived from rice husk filler (RHF) reinforced for polyvinyl chloride (PVC)/epoxidized natural rubber (ENR) blend was developed. RHF particles obtained as a byproduct from the agricultural industry were used as environmentally friendly fillers. ENR was applied as a plasticizer and compatibilizer to improve the compatibilization between PVC matrix and RHF. Regarding the influence of RHF content, RHF particle size, and ENR amount on the properties of such biocomposite, the mechanical and thermal properties were analyzed. The obtained results implied that the combination between PVC, ENR, and RHF in an optimized ratio of 90/10/20 (wt%) can produce a novel biocomposite with enhanced properties, which can offer good advantages for various applications in requirement of environmental protection.